Factors influencing lake surface water temperature variability in West Greenland and the role of the ice sheet - L. Carrea; C. J. Merchant; C. J. Merchant; R. I. Woolway; N. McCarroll; N. McCarroll (The Cryosphere)
Subarctic West Greenland is populated by thousands of seasonally ice-free lakes. Using remotely sensed observations, we analyse the surface water temperatures of six lakes during 1995–2022 to identify factors influencing their variability. The connectivity to the Greenland Ice Sheet (GrIS) has a clear influence on lake surface temperature, with ice-sheet-marginal lakes experiencing smaller average summer maximum temperature (<6 °C) and minimal interannual variability. A lake fed by a GrIS-originating river has the fastest seasonal response and largest seasonal amplitude with average maximum temperatures above 13 °C. The seasonal cycle of surface water temperature for all studied lakes is asymmetrical, with faster warming observed after ice-off and a slower cooling of water towards winter freezing. We find that during the study period, the onset of positive stratification occurred earlier, at rates of up to 0.5 d yr−1, and that July–August temperatures increased at rates up to 0.1 °C yr−1, although the GrIS-connected lakes show smaller increases. Our analysis suggests that the main meteorological factor determining interannual variability of surface water temperature in the studied lakes is air temperature. This study highlights the important role of remote sensing for long-term monitoring of Greenland lakes under climate change.